The use of social networks in the study of foreign languages at the university - L. D. Efanova; V. L. Polyakova (Вестник университета)
The analysis of the effectiveness of the use of communities in social networks for the study of foreign languages at the University both at the level of language and at the level of speech material has been conducted. The application of messengers for speaking practice with native speakers has been substantiated, which allows to overcome the language barrier, to train pronunciation, to replenish the vocabulary with modern language lexicon. It has been argued convincingly, that the use of social networks in the learning process leads to a change in the entire educational paradigm.